WEBINAR ONLINE MARKETING DALAM MENGHADAPI ERA NEW NORMAL BAGI GENERASI MUDA WIRAUSAHA - Ni Wayan Purnami Rusadi; Ni Wayan Dian Irmayani; Luh Lisa Suryantini (JPM17: Jurnal Pengabdian Masyarakat, 2021)
The Coronavirus (COVID-19) pandemic, which has occurred this year, paralyzes the activities of all people who are carried out outside the home. The impact of this pandemic has decreased the economy, and the unemployment rate has increased due to the fact that many companies have terminated their employment contracts. This period of the COVID-19 pandemic cannot be controlled quickly, so it requires proper management from both the government and the community to restore the economy. Therefore, the government established a new normal system. New normal is a change in behavior or habits to continue carrying out activities as usual but by always implementing health protocols in the midst of the COVID-19 pandemic.Entrepreneurship is a strong belief in a person to change the world through ideas, innovation and creativity. In this new normal era, having an entrepreneurial spirit is very important to restore the economy and to adapt to this situation. To adapt, we must follow business trends that are rising during this pandemic, for example, online businesses. During this pandemic, many people prefer to shop online because it is more efficient and prevents transmission of COVID-19. Therefore, online businesses are very developing during this pandemic and this business can awaken the spirit of entrepreneurship in the community, especially millennials so that they can adapt to this new normal era.The Synergy Accounting Seminar Volume 1 (NARASI # 1) will be held online on Thursday, May 6, 2021 through a video conference application, namely Google Meet, which is located at DNA (Dharma Negara Alaya). This webinar activity was attended by 265 people from accounting students majoring in UNDIKNAS Denpasar and the general public. Keywords: Online marketing, entrepreneurship, accounting webinar